A Chemistry and Microstructure Perspective on Ion‐Conducting Membranes for Redox Flow Batteries. Issue 47 (29th July 2021) - Xiong, Ping; Zhang, Leyuan; Chen, Yuyue; Peng, Sangshan; Yu, Guihua
Abstract: Redox flow batteries (RFBs) are among the most promising grid‐scale energy storage technologies. However, the development of RFBs with high round‐trip efficiency, high rate capability, and long cycle life for practical applications is highly restricted by the lack of appropriate ion‐conducting membranes. Promising RFB membranes should separate positive and negative species completely and conduct balancing ions smoothly. Specific systems must meet additional requirements, such as high chemical stability in corrosive electrolytes, good resistance to organic solvents in nonaqueous systems, and excellent mechanical strength and flexibility. These rigorous requirements put high demands on the membrane design, essentially the chemistry and microstructure associated with ion transport channels. In this Review, we summarize the design rationale of recently reported RFB membranes at the molecular level, with an emphasis on new chemistry, novel microstructures, and innovative fabrication strategies. Future challenges and potential research opportunities within this field are also discussed. Abstract : The membrane in redox flow batteries (RFBs) plays a critical role in their practical application. Promising RFB membranes require the deliberate design of their materials chemistry and microstructure. This Review highlights the design rationales of recently reported RFB membranes at the molecular level with in‐depth discussion of the structure–property relationships, and subsequently discusses future prospect in the field.